Efectos de la aplicación de insecticidas para el control del barrenadores del tallo en el cultivo de arroz (Oryza sativa L.) - Alejandro Alvear, Janio Jonni (2019)
This research work was carried out in the experimental farm “San Pablo”, of the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at Km 7.5 of the Babahoyo –Montalvo highway in the province of Los Ríos. The geographical coordinates are west longitude 790 32´, south latitude 010 49´ and altitude of 8 meters above sea level. The area has a humid tropical climate according to the Holdribge classification, with an annual temperature of 26.3 0C, rainfall of 2791.43 mm / year, relative humidity of 76% and 804.71 hours of annual average heliophile. Certified seeds of the INIAP 16 rice variety were used. The treatments studied were Clorantraniliprole + Thiamethoxam at a dose of 150 cc / ha; Alfacipermethrin + Teflubenzuron dose of 400 cc / ha; Benfuracarb + Xylene dose of 1000 cc / ha and Accept in doses of 1500 g / ha. The experimental design of Random Complete Blocks was used, with five treatments and four repetitions, the comparisons of the means were made with the Tukey test. All the necessary agricultural work was carried out in the cultivation of rice for its normal development as land preparation, planting, irrigation, fertilization, weed control, phytosanitary control and harvest. From the results obtained, it was determined that no populations of larvae and adults of Diatraea saccharalis and Elasmopalpus lignosellus were found during the course of the trial; R. albinella larvae and adult populations were controlled with the application of insecticides from 7 days after application; the control treatment without insecticide application showed greater mechanical damage with 57.5%; The agronomic characteristics of days to flowering, plant height, tillers and panicles / m2, panicle length, grains per panicle and weight of 1000 grains of the SFL-11 rice variety obtained better results with the use of Alfacipermethrin + Teflubenzuron dose of 400 cc / ha and the highest crop yield with 7255.0 kg / ha and net benefit of $ 690.03 was recorded with the application of Alfacipermethrin + Teflubenzuron dose of 400 cc / ha at 34 days after sowing.